Legal framework and guiding instruments of Management Plans in State Conservation Units, of sustainable use in Amazonas (Research, Society and Development, 2023)
The creation of Conservation Units (CU) and other categories of protected areas has been the main strategy for the in situ conservation of biodiversity. These geographical spaces are capable of promoting the conservation of biodiversity and keeping alive the traditional knowledge of the resident communities and users of it. In Brazil, the Management Plan, along with the management council, is considered as the fundamental instrument for the implementation of these protected areas, being defined as the technical and managerial document, based on the objectives of the CU, which establishes its Zoning, norms that should regulate the use of the area and the management of natural resources, including the implementation of the physical structure necessary for the management of the Unit. The specific objective of this research was to understand the way in which the management plans for the studied Conservation Units were elaborated. In order to evaluate the effectiveness of the Management Plans in Amazonas, a content analysis was conducted in the documents that prescribe and discipline the theme, with attention to the 2nd edition of the methodological roadmap for the elaboration of management plans adopted by the state government, as well as semi-structured interviews with the managers (members of the management council and with the managers of the conservation units studied) that act directly in the management of these CUs.